MODEL OF EXPERT ASSESSMENT OF THE LEVEL OF INFLUENCE OF HUMAN RESOURCES ON TOURIST SATISFACTION WITH THE DESTINATION - SHAFAR, ANDRIY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
In modern conditions, tourism plays an important role in economic development, forming a positive image of destinations and ensuring the sustainable development of regions. One of the key factors influencing tourist satisfaction with a destination is the quality of work of human resources, which directly interacts with clients and provides tourist services. However, existing approaches to assessing the impact of human resources on tourist satisfaction are mostly fragmentary and do not sufficiently consider the complexity of this process. The main goal of the study is to develop a model for expert assessment of the level of impact of human resources on tourist satisfaction with a destination. The study is based on modern mathematical methods of fuzzy set theory, which allow to effectively consider uncertainty in client reasoning, process linguistic inferences and obtain initial estimates using comparative values. This mathematical toolkit helps to increase the validity of management decision-making. The main value of the model is that it comprehensively analyzes the problem of employee loyalty in the tourism business, covering both accommodation establishments and the tourism industry within the entire region. In addition, all model settings were based on real data. The model was tested on real data collected from 327 respondents in Zakarpattia, Lviv, and Ivano-Frankivsk regions. The results will help tourists choose vacation destinations with high levels of service, which will increase their experience and the likelihood of repeat visits. Businesses will be able to improve service quality, optimize human resource management and develop strategies to enhance the tourist experience. Regional authorities will use this data to develop infrastructure, training initiatives and policies that increase the competitiveness of tourist destinations.